Clinical evaluation of the self-administered psoriasis area and severity index (SAPASI) - Szepietowski, J... C. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
Introduction: Psoriasis Area and Severity Index (PASI) is used by dermatologists to assess psoriasis disease intensity. The Self-Administered Psoriasis Area and Severity Index (SAPASI) was developed to allow patients to evaluate the intensity of psoriasis by themselves. Objectives: This study was undertaken to evaluate the validity and usefulness of the SAPASI scoring method in Polish psoriatic patients. Material and methods: 51 patients suffering from psoriasis were included into the study. PASI assessment was performed by trained staff and the Extent Score from Salford Psoriasis Index (SPI) was calculated. Moreover, the patients were asked to complete SAPASI evaluation. The studied indexes, as well as their elements (area involvement, severity), were compared using Spearman rank correlation test. Results. SAPASIsignificantly correlated with PASI and Extent Score from SPI for the whole group of patients. Both females and males assessed their total skin symptoms (SAPASI) similarly to PASI evaluation, however stronger correlation between SAPASI and PASI was found for female than male patients. There was no significant correlation between severity SAPASI and severity PASI when assessed by male patients. The age of patients did not influence their evaluation of skin lesions. Patients with longer history of psoriasis assessedintensity of the disease more accurately than those with shorter duration of psoriasis.
Keywords: Psoriasis; Self administration; Severity of illness index